Fixed asset management of Robi Axiata Limited and the financial analysis of Axiata Group Berhad - Ahmed, Jahran (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.